Enhancing a Nheengatu Morphosyntactic Analyzer for Word Formation and Non-standard Language - Alencar, Leonel Figueiredo de (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2025: Anais do XVI Simpósio Brasileiro de Tecnologia da Informação e da Linguagem HumanaDO - 10.5753/stil.2025.37810, 2025)
UD_Nheengatu-CompLin is the highest-rated and second-largest Amerindian language treebank in Universal Dependencies. It is annotated with Yauti, an analyzer for Nheengatu that uses special tags to handle unknown words. This paper presents a major revision of the special tag mechanism, extending coverage to phenomena such as reduplication, typos, and stylistic variation. A multi-level validator was implemented and passed 416 test cases. All 231 treebank sentences with special tags parsed, yielding a macro F1 score of 0.92 and both weighted and micro F1 scores of 0.96 in feature assignment.